Efficacy of Methylprednisolone Pulse Followed by Oral Prednisone in Birdshot Chorioretinopathy. (3rd September 2017) - Hafidi, Meriem; Loria, Olivier; Kodjikian, Laurent; Denis, Philippe; Ferrand, Muriel R.; Broussolle, Christiane; Sève, Pascal
ABSTRACT: Purpose : To report the outcomes of initial methylprednisolone pulse then oral prednisone in the treatment of birdshot chorioretinopathy (BSCR). Methods : We retrospectively reviewed medical records of 21 BSCR patients, treated with initial methylprednisolone, prednisone, or immunosuppressive therapy. Main outcome measures were changes in visual acuity, intraocular inflammation, concomitant immunosuppressive drug or intravitreal steroid, and adverse events. Results : In total, 14 patients were initially treated with methylprednisolone; four patients with prednisone; and three with immunosuppressive drug. Intraocular inflammation was controlled in 10 of 14 patients (71%) at 1 year, with a mean dose of 6.2 mg/day prednisone. Patients treated initially by methylprednisolone had improved visual acuity at 1 year, but it was not significantly different from patients treated initially by prednisone. Conclusions : Corticosteroid therapy, including initial methylprednisolone pulse then prednisone, was effective in stabilizing vision and decreasing inflammation in most patients with BSCR.